Relationship between the Concentration of Supplemental Oxygen and Signal Intensity of CSF Depicted by Fluid-Attenuated Inversion Recovery Imaging - Braga, Flávio T.; da Rocha, Antônio J.; Filho, Guinel Hernandez; Arikawa, Renê K.; Ribeiro, Ivone M.; Fonseca, Ricardo B. (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Prior reports have described increased signal intensity (SI) of CSF on fluid-attenuated inversion recovery (FLAIR) images of anesthetized patients receiving 100% O2. This appearance can simulate that of diseases. We evaluated the relationship between the concentration of inhaled O2 and the development of increased SI of CSF on FLAIR images.METHODS: FLAIR was performed in 25 healthy volunteers breathing room air and 100% O2 through a face mask for 5, 10, and 15 minutes. MR imaging, including FLAIR imaging, was performed in 52 patients with no potential meningeal abnormalities under general anesthesia: 21 received an equal mixture of N2O and O2, and 31 received 100% O2. The SI of CSF in volunteers and patients was graded in several locations by using a three-point scale.RESULTS: SI of CSF significantly increased (P < .05) in various locations, in both volunteers and patients breathing 100% O2, when compared with SI in the same volunteers breathing room air. Hyperintensity of CSF was not significantly different in volunteers receiving 100% O2 through a face mask compared with anesthetized patients receiving 100% O2 through a laryngeal airway or an endotracheal tube. No significant increase in SI occurred in patients receiving 50% O2, when compared with the SI of volunteers breathing room air.CONCLUSION: Supplemental oxygen at 100% is a main cause of artifactual CSF hyperintensity on FLAIR images, regardless of the anesthetic drug used. This artifact does not develop when 50% O2 is administered.